Propuesta para el aprovechamiento de residuos orgánicos en el municipio de Alvarado Tolima (2020)
Solid waste has always existed, the difference between today and the past is that before there was less population, less use of embolisms or containers made of non-degradable or environmentally friendly material and greater availability of land to deposit the waste that is They threw after selecting what could serve. Today, with the growth and concentration of the population in urban areas and the development of economic and social activity, the generation of products is greater, which at the same time increases the production of waste, and as they are not intervened with utilization processes, they are considered junk, which makes them look worthless. These wastes are classified according to their origin, their composition and their impact on the environment. The increase in waste generation has a negative impact on the environment, which has made the national government generate policies for intervention, through prevention, control and mitigation strategies for the protection of the environment. That is why the following project aims to make a proposal for the use of organic waste in the municipality of Alvarado, Tolima through the composting process.